The Estado de Minas newspaper's communist - Barcelos, Lucas (Em Perspectiva, 2021)
This article seeks to understand the relationship between the newspaper Estado de Minas and the chronicler Roberto Drummond, based on the concept of “accommodation”,during the Brazilian civil-military dictatorship. For this, from sources of the newspaper, I analyzed how a journal that supported the 1964 Brazilian coup d'état, supported the dictatorship until the early 1980s, had a well-known communist in its staff, using the idea of ​​accommodation as part of the Brazilian political culture. Through an introduction to the Estado de Minas newspaper, the association with conservative and later coup governments in 1964 is clear, in addition to support for dictators. Roberto Drummond enters as a “communist elemento” precisely because he was hired in na authoritarian period, writing sports chronicles that attack the political management of the Brazilian team, but not directly the dictators. Finally, it is concluded that the two sides of this game give up positions for the possible benefits of the association.